Pengaruh Waktu Dan Massa Terhadap Penyerapan Logam Fe Dalam Air Gambut Menggunakan Adsorben Sekam Padi - Jannah, Roudhatul; Daud, Syarfi; Edward, Edward (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Rice husk is an abundant agricultural waste and has the potential to be used as a source of activated carbon for adsorbents. The purpose of this study was to determine the efficiency of removal of Fe in peat water, calculate the adsorption capacity, and compare with the quality standards of the Republic of Indonesia Ministry of Health No. 416 / MENKES / PER / IV / 2010 concerning drinking water quality standards. The fixed variables used in this study were stirring speed 180 rpm, carbonization temperature of 250oC, sieve size of 70 mesh, and HCL 4N activator. The independent variables used consisted of variations in mass of adsorbent 1; 1.5; 2; 2.5 grams and variations in time 30, 60, 90 and 120 minutes. The removal efficiency of Fe metal concentration was 79.7% in the mass of 2.5gr adsorbent with a contact time of 30 minutes. The highest adsorption capacity of Fe metal was achieved at 1gr mass with 90 minutes contact time of 0.212 mg Fe / gr. The results showed that Fe parameters were in accordance with Permenkes No. 416 / MENKES / PER / IV / 2010. Keywords: Adsorption, Adsorbent, Peat Water, Rice Husk